Down‐regulation of TIMP2 by HIF‐1α/miR‐210/HIF‐3α regulatory feedback circuit enhances cancer metastasis in hepatocellular carcinoma - Kai, Alan Ka‐Lun; Chan, Lo Kong; Lo, Regina Cheuk‐Lam; Lee, Joyce Man‐Fong; Wong, Carmen Chak‐Lui; Wong, Jack Chun‐Ming; Ng, Irene Oi‐Lin (Hepatology (Baltimore, Md.), 2016)
Cancer metastasis is a multistep process that involves a series of tumor‐stromal interaction, including extracellular matrix (ECM) remodeling, which requires a concerted action of multiple proteolytic enzymes and their endogenous inhibitors. This study investigated the role of tissue inhibitor of metalloproteinases (TIMP) 2 in the context of hepatocellular carcinoma (HCC) metastasis. We found that TIMP2 was the most significantly down‐regulated member among the TIMP family in human HCCs. Moreover, TIMP2 underexpression was frequent (41.8%; 23 of 55) in human HCCs and was significantly associated with liver invasion and poorer survival outcomes of HCC patients. Furthermore, stable silencing of TIMP2 in HCC cell lines enhanced cell invasive ability and ECM degradation associated with formation of invadopodia‐like feature, suggesting that TIMP2 is a negative regulator of HCC metastasis. Using an orthotopic tumor xenograft model, we demonstrated that ectopic expression of TIMP2 open reading frame in the highly metastatic HCC cell line, MHCC‐97L, significantly reduced HCC progression as well as pulmonary metastasis. Mechanistically, TIMP2 suppression, in a hypoxic environment, was induced through a regulatory feedback circuit consisting of hypoxia‐inducible factor (HIF) 1 alpha, microRNA‐210 (miR‐210), and HIF‐3α. Conclusion: TIMP2 is frequently down‐regulated in human HCCs and its down‐regulation is associated with aggressive tumor behavior and poorer patient outcome. Its suppression is under the regulation of a novel feedback circuit consisting of HIF‐1α/miR‐210/HIF‐3α. TIMP2 is an important regulator of ECM degradation and HCC metastasis. (Hepatology 2016;64:473‐487)